Untranslated Gene Regions and Other Non-coding Elements Regulation of Eukaryotic Gene Expression - Barrett, Lucy W.; Fletcher, Sue.; Wilton, Steve D.; SpringerLink (Online service) (Basel : Springer Basel : Imprint: Springer, 2013)
There is now compelling evidence that the complexity of higher organisms correlates with the relative amount of non-coding RNA rather than the number of protein-coding genes. Previously dismissed as (3z(Bjunk DNA(3y(B, it is the non-coding regions of the genome that are responsible for regulation, facilitating complex temporal and spatial gene expression through the combinatorial effect of numerous mechanisms and interactions working together to fine-tune gene expression. The major regions involved in regulation of a particular gene are the 5$1 (Band 3$1 (Buntranslated regions and introns. In addition, pervasive transcription of complex genomes produces a variety of non-coding transcripts that interact with these regions and contribute to regulation. This book discusses recent insights into the regulatory roles of the untranslated gene regions and non-coding RNAs in the control of complex gene expression, as well as the implications of this in terms of organism complexity and evolution.s
Introduction -- Promoter -- 5$1 (BUntranslated Region -- Structure -- Intronic Regions -- 3$1 (BUntranslated Region -- Non-coding RNAs -- Conclusion.s
Keywords: Life sciences; Medical genetics; Nucleic acids; Plant genetics; Animal genetics; Life Sciences; Animal Genetics and Genomics; Plant Genetics & Genomics; Gene Function; Nucleic Acid Chemistry; Electronic books